A brief review of potential neuroprotective roles of the culinary herb Ocimum basilicum - Manali Haniti MZ; Juriyati Jalil; Chan, KM; Norazrina Azmi (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Neurodegenerative diseases commonly affect elderly population and are characterised by progressive neuronal loss. Oxidative stress is highly associated with neurodegeneration. The targeted herbal plant in this review, Ocimum basilicum (O. basilicum), is typically used in Indochina and Italian cuisine. Pharmacological studies on O. basilicum have demonstrated potent antioxidant activities with some reports of neuroprotective actions. This brief review highlights the potential neuroprotective roles of O. basilicum by discussing previously documented antioxidative actions of the plant extract, essential oils and its phytochemical compounds on the nervous system based on in vitro and in vivo studies. Accumulating evidence on the neuroprotective action of O. basilicum points to a notion that neuroprotection is made possible by way of its antioxidant properties and largely due to the presence of polyphenol compounds such as rosmarinic acid which has been identified as the major constituent. Although the mechanisms of O. basilicum antioxidant action have been proposed, further studies are required for better understanding of its antioxidant action leading to neuroprotective roles. It is also possible that the antioxidant actions of O. basilicum are mediated through synergism of a mixture of various naturally-occurring bioactive compounds in the plant, as is with many other plant-based food supplements, to produce the putative effects instead of a single bioactive compound from the plant. Therefore, specific targeting of neuroprotection by means of antioxidant actions warrants further preclinical and clinical studies investigating the therapeutic potentials of O. basilicum particularly in view of the prevention of neurodegenerative processes.